Nicardipine-Induced Acute Pulmonary Edema: A Rare but Severe Complication of Tocolysis - Claire Serena; Emmanuelle Begot; Jérôme Cros; Charles Hodler; Anne Laure Fedou; Nathalie Nathan-Denizot; Marc Clavel (Case Reports in Critical Care)
We report four cases of acute pulmonary edema that occurred during treatment by intravenous tocolysis using nicardipine in pregnancy patients with no previous heart problems. Clinical severity justified hospitalization in intensive care unit (ICU) each time. Acute dyspnea has begun at an average of 63 hours after initiation of treatment. For all patients, the first diagnosis suspected was pulmonary embolism. The patients' condition improved rapidly with appropriate diuretic treatment and by modifying the tocolysis. The use of intravenous nicardipine is widely used for tocolysis in France even if its prescription does not have a marketing authorization. The pathophysiological mechanisms of this complication remain unclear. The main reported risk factors are spontaneous preterm labor, multiple pregnancy, concomitant obstetrical disease, association with beta-agonists, and fetal lung maturation corticotherapy. A better knowledge of this rare but serious adverse event should improve the management of patients. Nifedipine or atosiban, the efficiency of which tocolysis was also studied, could be an alternative.